(untitled) (The Pakistan Development Review, 2004)
Solar photovoltaic systems are prohibitively expensive in terms of installation costs. Power from them is also available intermittently—only when energy from the sun is available. On the other hand, PV systems are free of the ever-rising costs of input fuel. They also incur much less operation and maintenance costs and are supposed to have a longer lifetime than, for example, a fossil fuel power plant. Thus using solar-PV power looks uneconomical in the short term, but may be profitable in the long term. It is, therefore, interesting to identify the factors that can make investment in solar PV power generation acceptable. This paper carries out a financial analysis of installing a 10 MW solar photovoltaic power generation plant for sale of electricity to a grid. It compares the levelised cost of this mode of energy generation as compared to a fossil fuel plant. It also calculates the cost of electricity generation and tariff for power from this plant. It then identifies the factors that can make the investment in a grid-scale solar PV plant more favourable than investment in other conventional and non-renewable sources.